Applying the Smooth Transition Autoregressive Model for Discovering the Nonlinear Cointegration Relationship Between the Interest Rate and Inflation in Vietnam - Nguyen, Ha Thanh (Journal of Applied Data Sciences, 2025)
Interest rates and inflation are two key macroeconomic indicators that have a direct impact on a country’s economy. The Fisher hypothesis addresses the relationship between these two variables, with its core idea being that nominal interest rates and inflation have a positive long-term relationship, while real interest rates remain constant. The primary objective of this study is to explore the relationship between interest rates and inflation in Vietnam during the period from 2007 to 2023. Unlike previous studies, this research, based on Vietnam's specific context, employs the Smooth Transition Autoregressive (STAR) model. This approach allows for testing nonlinear cointegration, overcoming the limitations of traditional cointegration methods. The study identifies that interest rates and inflation exhibit long-term co-movement, adhering to a common trend. When these two variables deviate from their equilibrium position, they rapidly adjust back to equilibrium, governed by an asymmetric logarithmic transition function. The findings challenge the one-to-one relationship proposed by the Fisher hypothesis, revealing a more complex link between interest rates and inflation. Additionally, the study highlights the interactive nature of Vietnam’s monetary and financial markets. It demonstrates that monetary policy tools can influence the financial market, while the long-term nominal interest rate emerges as a potential indicator of inflation. These insights provide significant implications for policymakers aiming to stabilize the economy through effective monetary and financial strategies. This research further confirms the effectiveness of nonlinear cointegration methods and the STAR model in macroeconomic analysis. The article also presents an interesting finding regarding the Fisher hypothesis in a developing country like Vietnam.